Performance of Ferroelectric Materials in the Construction of Smart Manufacturing for the New Infrastructure of Smart Cities - Minggui Zhou; Gongxing Yan (Advances in Materials Science and Engineering)
Smart city construction is the inevitable product of scientific development and transformation of life by building digital cities, building the Internet of Things, and making city management systems simple and intelligent through cloud computing. Smart city is a new generation information technology. Make full use of the advanced form of urban informatization based on the next generation innovation of knowledge society in all walks of life in the city. Cloud computing is a new network application concept. The core concept of cloud computing is to take the Internet as the center, and provide fast and secure cloud computing services and data storage on the website, so that everyone who uses the Internet can use the huge computing resources and data center on the network. The role of smart city engineering infrastructure is to build the infrastructure of this platform, so that smart cities can operate effectively, such as deformation test of ferroelectric materials, particle suitability analysis of ferroelectric materials, etc., This research is oriented to the intelligent manufacturing of new infrastructures in smart cities and analyzes the performance of ferroelectric materials in construction, aiming to better grasp the performance of ferroelectric materials and provide constructive suggestions for smart manufacturing in smart cities. The article first understands and states the related concepts, related construction requirements, development status and problems that need to be solved for smart city smart manufacturing by consulting relevant materials; then, it discusses the ferroelectric materials involved in the construction, analyzes the data of piezoelectric properties, etc., which will help to give more clear guidance on the process of tooling design; finally, the application link of ferroelectric materials is tested, and the deformation of ferroelectric materials and this premise are discussed on the problem of intelligent manufacturing efficiency and intelligent manufacturing efficiency. The experimental results show that the maximum value in the group of smart manufacturing benefits is 559.37; the maximum value between groups is 172.35. For efficiency of smart manufacturing, the maximum value between groups reaches 187.07; the maximum value in groups is 286.35. Whether it is a significant analysis of smart manufacturing benefits or smart manufacturing efficiency, the experimental results are quite impressive.